(untitled) - Saint-Gilles, Amaury (Tokyo, 1983)
Book introduced and reacquainted about Mingei Japan's folk arts through the eyes of Amaury Saint-Giles
Keywords: Folk art,Nghệ thuật dân gian; Japan,Nhật Bản